Modern Trends in the Development of the Rural Environment and Rural Settlement in Siberia - Pustovetov, Gennady; Likhachev, Eugeny; Parshukova, Galina; Erokhin, Grigory; Likhacheva, Alla (project baikal, 2019)
The article is devoted to modern trends in the development of rural space, the characteristics of rural architecture on the example of Western Siberia. The dependence of planning decisions and architectural features in the countryside on lifestyle is indicated. It is revealed that a change in the rural lifestyle affects the change in the architecture of the rural manor house. The conclusion is made: the study of the settlement systems and the architectural environment of various territories should be considered not only in the context of the natural environment, but also in the context of the socio-cultural dynamics of the area.
Keywords: rural environment; rural settlement; Siberia; rural architecture; rural lifestyle